Rheological properties and rutting performance of waste incorporated hybrid asphalt binders - Wan Noor Hin, Mior Sani; Putra Jaya, Ramadhansyah; Khairil Azman, Masri; Dulaimi, Anmar; Norhidayah, Abdul Hassan (Springer, 2025)
Intense efforts have been focused on formulating excellent asphalt mixtures to achieve desirable properties in line with the growing numbers of traffic loads and harsh environmental factors. Nevertheless, the complex rheological behaviour of modified asphalt binders makes it challenging to predict their consistent performance, especially when incorporated with waste materials. In view of the promising use of valuable waste materials in asphalt mixtures, this study examined the rheological characteristics and rutting performance of hybrid asphalt binders incorporated with Palm Oil Fuel Ash (POFA), garnet waste, and sawdust as asphalt modifiers. A Dynamic Shear Rheometer (DSR) with frequency sweep test was used to compare the performance of individual-modified asphalt binders comprising 3% of POFA, garnet waste, and sawdust, respectively, and 0%, 3%, 6%, and 9% hybrid content combining the three waste materials in unaged hybrid asphalt binders and Rolling Thin Film Oven (RTFO) hybrid asphalt binders. The Multiple Stress Creep Recovery (MSCR) test was utilised to assess the creep and recovery properties of the asphalt mixtures, while the complex shear modulus (G*) and phase angle (δ) master curves were constructed to evaluate the viscoelastic performance of the asphalt mixtures. Comparatively, the creep recovery rate of the 6% unaged hybrid asphalt binder was substantially higher compared to its 3% and 9% unaged hybrid asphalt binder. According to the master curve analysis, the improved performance of the 6% RTFO hybrid asphalt binder is evident in the low frequency, which corresponds to the extremely high-temperature conditions. In summary, the addition of 6% hybrid content in the short-term aged RFTO hybrid asphalt binders achieved high creep recovery and high-temperature susceptibility and is considered the optimum asphalt mixture to achieve sustainable and high-performance asphalt pavements.